2021
DOI: 10.1016/j.jid.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Slac2-b Coordinates Extracellular Vesicle Secretion to Regulate Keratinocyte Adhesion and Migration

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…(3) Exophlin-5/Slac-b Genetic mutation of exophilin-5 causes an autosomal recessive form of epidermolysis bullosa simplex that results in skin fragility and erosions (McGrath et al, 2012). Although the molecular pathogenesis is largely unknown, exophilin-5-deficient keratinocytes exhibit defects in cell adhesion and reduced secretion of extracellular vesicles containing extracellular matrix proteins (Bare et al, 2020), consistent with the reported role of exophilin-5 in exosome secretion (Ostrowski et al, 2010). It has recently been shown that exophlin-5 knockout mice exhibit increased allergic airway inflammation (Okunishi et al, 2020).…”
Section: The Structure and Function Of Rab27 Effectorsmentioning
confidence: 99%
“…(3) Exophlin-5/Slac-b Genetic mutation of exophilin-5 causes an autosomal recessive form of epidermolysis bullosa simplex that results in skin fragility and erosions (McGrath et al, 2012). Although the molecular pathogenesis is largely unknown, exophilin-5-deficient keratinocytes exhibit defects in cell adhesion and reduced secretion of extracellular vesicles containing extracellular matrix proteins (Bare et al, 2020), consistent with the reported role of exophilin-5 in exosome secretion (Ostrowski et al, 2010). It has recently been shown that exophlin-5 knockout mice exhibit increased allergic airway inflammation (Okunishi et al, 2020).…”
Section: The Structure and Function Of Rab27 Effectorsmentioning
confidence: 99%
“…Keratinocytes expressing mutant Slac2‐b or with Slac2‐b knocked out showed reduced release of exosome vesicles containing extracellular matrix. Additionally, CD63 + vesicles, which were correlated with focal adhesion dynamics, were mislocalized in Slac‐2b‐depleted cells 10 . Taken together, it is plausible that Slac‐2b contributes to epidermal integrity through focal adhesions, which might explain the milder form of blistering in EB patients with EXPH5 mutations.…”
Section: Discussionmentioning
confidence: 92%
“…Although these genes lack previous reports of direct association with NSOFCs phenotypes, they have been implicated in processes crucial for craniofacial development. The EXPH5 gene, for instance, has been shown to play a role in cell-cell adhesion 32 ; a critical process in craniofacial morphogenesis.…”
Section: Discussionmentioning
confidence: 99%